Pertanggungjawaban Notaris atas Kebenaran Akta Otentik: Studi Putusan MA No. 379K/Pid/2021 - Tapsirudin, Tapsirudin; Zulfa Aulia, M.; Abu Bakar, Firdaus (Magister Kenotariatan, Universitas Jambi, 2026)
An authentic deed drawn up by a notary functions as an evidentiary instrument that ensures legal certainty and protection for the parties. In notarial practice, problems arise when a deed formally complies with legal requirements but fails to reflect the actual legal transaction. This condition raises debates concerning the scope of a notary’s responsibility for the formal and material accuracy of an authentic deed. This study aims to analyze the legal regulations governing notarial responsibility and to examine the form of legal liability as reflected in Supreme Court Decision Number 379 K/Pid/2021. This research employs a normative juridical method using statutory, conceptual, and case approaches. The findings indicate that the Notary Office Act does not clearly define the obligation of notaries to guarantee material truth. The Supreme Court interprets that a notary may incur criminal liability when he or she is aware of discrepancies between the substance of the deed and the parties’ actual legal acts. This interpretation generates legal uncertainty and requires normative clarification.